"Dial‐In" Emission from a Unique Flexible Material with Polarization Tuneable Spectral Intensity. Issue 59 (13th September 2019) - Kumar, Rajan; Ray, Subir Kumar; Mukherjee, Saikat; Saha, Sudipta; Bag, Arijit; Ghorai, Pradip Kr.; Ghosh, Nirmalya; Shunmugam, Raja
Abstract: The development of organic photoluminescent materials, which show promising roles as catalysts, sensors, organic light‐emitting diodes, logic gates, etc., is a major demand and challenge for the global scientific community. In this context, a photoclick polymerization method is adopted for the growth of a unique photoluminescent three‐dimensional (3D) polymer film, E, as a model system that shows emission tunability over the range 350–650 nm against the excitation range 295–425 nm. The DFT analysis of energy calculations and π‐stacking supports the spectroscopic observations for the material exhibiting a broad range of emission owing to newly formed chromophoric units within the film. Full polarization spectroscopic Mueller matrix studies were employed to extract and quantify the molecular orientational order of both the ground (excitation) and excited (emission) state anisotropies through a set of newly defined parameters, namely the fluorescence diattenuation and fluorescence polarizance. The information contained in the recorded fluorescence Mueller matrix of the organic polymer material provided a useful way to control the spectral intensity of emission by using pre‐ and post‐selection of polarization states. The observation was based on the assumption that the longer lifetime of the excited dipolar orientation is attributed to the compactness of the film. Abstract : Crosslinked framework : A photoclick polymerization method is adopted for the growth of a unique photoluminescent 3D polymer film, E, as a model system that shows emission tunability over the range 350–650 nm against the excitation range 295–425 nm. The DFT analysis of energy calculations and π‐stacking supports the spectroscopic observations for the material exhibiting a broad range of emission owing to newly formed chromophoric units within the film.